Efeito do estrato de semente de uva na adesão de pinos de fibra de vidro à dentina radicular - Silva, Gabrielle de Carli da (2015)
Endodontically treated teeth can present a great loss of dental structure. In some times, it is necessary to use an intraradicular dental post to retain the coronal restoration. Resin cements are frequently used to bond fiber glass posts into the root canals, however the hybrid layer degradation can lead to bond failures overtime. In this way, the aim in this study was investigate the bond strength of fiber glass post cemented with self-adhesive resin cement after pre-treatment of root canal with grape seeds extract (GSE) in different times and concentrations. Eighty-four maxillary canines were used (n=6). Dentin was pretreated with 6.5% or 10% GSE for 30s, 60s, or 120s. No pre-treatment was done in the control group. Fiber glass posts were cemented with RelyX U200. The root canals were sectioned into 6 slices of 1mm thickness approximately , obtaining 2 samples from each third (cervical, medium and apical). The specimens were submitted to a push-out test in a Universal Testing Machine at 1mm/min until failure. Bond strength was calculated and expressed in MPa. In half of the samples the bond strength test was performed after 24 hours (immediate group) and the other half, after 12 months storage in distilled water (mediate group). The bond strength values were statically analyzed by ANOVA test. No significant difference was detected between the different application times and concentrations used for the pre- treatment (p>0.05). GSE extract did not change the bond strength in all groups analyzed.